Effectiveness of cardiopulmonary resuscitation training in the learning of Pedagogy students (Research, Society and Development, 2024)
Introduction: In the school environment, teachers trained in Basic Life Support contribute to a safer community by promoting a culture of prevention and quick responses to emergencies. Objective: To demonstrate the effectiveness of Basic Life Support training in the learning of Pedagogy students enrolled at a public university in the city of Ponta Grossa/PR. Methodology: This is a quasi-experimental study with a quantitative approach. The study was conducted in three stages: 1. Pre-test, assessing the students' prior theoretical knowledge of adult CPR; 2. Application of Basic Life Support training through a lecture and simulation; 3. Post-test, using the same instrument from the first phase. The McNemar Exact Test was used for statistical analysis, with a significance level of 5%. Results: 81 students participated, with a predominance of females (96.3%) and an average age of 27.92 years. Most participants (81.5%) had never received BLS training. The accuracy rate in the post-test significantly increased compared to the pre-test. Conclusion: The training was effective for the students, with better performance in the post-test. This highlights the importance of incorporating Basic Life Support training into university curricula, preparing future educators for emergencies and promoting a safer school environment.